PLAGIARSM: MENGAPA HARUS TERJADI? - FX Supriyono (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
The purpose of this article is to describe a hot issue called plagiarism. Even though, this is not a simple matter and even some people said that it is a mission impossible, higher education should participate to overcome the problem. The problems of plagiarism exist 'because of many reasons. First it is caused by internal factors, such as personality; values and low appreciation of science. Second it is merely 'caused by external factors such as education system, promotion system, character building, reading habits and control of the institution. Therefore, several steps should be taken, such as emphasizing of the character building in the process of learning; providing the system control and improving the process of consultation. By doing this steps, it is possible to minimize that deviant behavior.